Aging-resistant aluminum alloy cable and a method for manufacturing the same
Patent Information
- Application Number
- CN202611268876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明提出一种耐老化铝合金电缆及其制备方法,解决了相关技术中铝合金电缆耐老化性能不足的问题
本发明中,沸石负载金属氧化物加入到铝合金电缆的外护套中,可以提升铝合金电缆的外护套的长期耐老化性能并减少小分子抗氧剂、紫外线吸收剂的用量;存在于沸石中的金属氧化物(氧化锆和/或氧化镁)在热氧老化过程可以捕捉材料降解产生的自由基,阻断自由基链式反应,提高材料的抗热氧老化能力;且氧化锆和/或氧化镁可以有效屏蔽紫外辐射,减少紫外光对聚乙烯分子链的直接破坏;沸石的多孔结构可物理散射紫外光,进一步降低紫外能量对基体的损伤。相较于小分子抗氧剂,氧化锆和/或氧化镁被锚定在沸石上,不会发生迁移、挥发或析出,可以长期稳定发挥作用;沸石还可通过物理吸附与化学吸附作用,吸附并固定外护套中的小分子抗氧剂、紫外线吸收剂,又进一步避免其在高温、紫外环境下向材料表面迁移、析出,避免了小分子抗氧剂、紫外线吸收剂在长期使用中因迁移现象出现的耐老化性能显著降低的情况出现。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, specifically to an aging-resistant aluminum alloy cable and its preparation method. Background Technology
[0002] Aluminum alloy cables, with their advantages of being lightweight, corrosion-resistant, and cost-effective, are widely used in power systems, building engineering, new energy, and industrial fields. They cover scenarios such as urban power distribution networks, high-rise building wiring, photovoltaic power stations, chemical industrial parks, and rail transit. They can replace traditional copper cables for power transmission, are adaptable to various complex indoor and outdoor environments, and meet the power supply needs of different scenarios. They are one of the important products in the current power transmission field.
[0003] Existing aluminum alloy cables typically have small-molecule antioxidants and ultraviolet absorbers added to their outer sheaths to meet basic aging resistance requirements. However, during long-term use, these small-molecule antioxidants and ultraviolet absorbers are prone to migration and volatilization, leading to additive failure. This, in turn, causes cracking, hardening, and powdering of the cable's outer sheath, and accelerates conductor oxidation. Under harsh outdoor environments with strong ultraviolet radiation and temperature fluctuations, the cable's service life is significantly shortened, making it difficult to meet the requirements for long-term stable operation. Summary of the Invention
[0004] This invention proposes an aging-resistant aluminum alloy cable and its preparation method, which solves the problem of insufficient aging resistance of aluminum alloy cables in related technologies.
[0005] The technical solution of the present invention is as follows: This invention proposes an aging-resistant aluminum alloy cable, which comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath. The cable core consists of an aluminum alloy conductor and an insulation layer from the inside out; The outer sheath comprises the following components in parts by weight: 90-100 parts polyethylene, 3-6 parts maleic anhydride-grafted linear low-density polyethylene, 0.1-0.2 parts antioxidant, 0.2-0.3 parts ultraviolet absorber, and 3-5 parts zeolite-supported metal oxide. The raw materials for the zeolite-supported metal oxide include metal salts and zeolite; the metal salts include magnesium salts and / or zirconium salts.
[0006] As a further technical solution, the method for preparing the zeolite-supported metal oxide includes the following steps: S1. Add zeolite to an acidic solution and mix once, centrifuge and wash once, then mix with ammonium nitrate solution a second time, centrifuge a second time, wash and dry to obtain pretreated zeolite; add water to metal salt to obtain metal salt solution; S2. Add the pretreated zeolite to the metal salt solution, adjust the pH to 7-8, impregnate, dry, grind, and calcine to obtain the zeolite-loaded metal oxide.
[0007] As a further technical solution, the zeolite includes 4A zeolite or clinoptilolite.
[0008] As a further technical solution, the mass-to-volume ratio of the zeolite to the acidic solution is 30g:90~100mL.
[0009] As a further technical solution, the acidic solution includes a 1.0 mol / L HNO3 solution.
[0010] As a further technical solution, the rotation speed of the primary mixing and the secondary mixing are each independently 200~300 rpm, and the time is each independently 3.5~4.5 h.
[0011] As a further technical solution, the rotation speed of the first centrifugation and the second centrifugation are each 2500~3500 rpm, and the time is each 5~6 min.
[0012] As a further technical solution, the mass-to-volume ratio of the zeolite and the ammonium nitrate solution is 30g:90~100mL.
[0013] As a further technical solution, in step S1, the drying temperature is 100~110℃ and the time is 6~7h.
[0014] As a further technical solution, the concentration of the metal salt solution is 0.05~0.1mol / L.
[0015] As a further technical solution, the mass-to-volume ratio of the pretreated zeolite to the metal salt solution is 30g:90~100mL.
[0016] As a further technical solution, the impregnation time is 5.5~6.5h.
[0017] As a further technical solution, in step S2, the drying temperature is 60~80℃ and the time is 10~12h.
[0018] As a further technical solution, the calcination temperature is 400~450℃, the time is 4~5h, and the atmosphere is a nitrogen atmosphere.
[0019] As a further technical solution, when the metal salt includes magnesium salt and zirconium salt, the molar ratio of magnesium salt to zirconium salt is 2~4:1, preferably 3:1.
[0020] In the outer sheath of this invention, the optimal combination of zeolite-loaded zirconium oxide and magnesium oxide provides the best long-term aging resistance for aluminum alloy cables. Zirconia, rich in Lewis acidic sites, efficiently adsorbs and stabilizes reactive free radicals generated during aging, preventing chain reactions and thus focusing on resistance to thermo-oxidative aging. Magnesium oxide, on the other hand, focuses on resistance to ultraviolet aging. Simultaneously, the porous structure of zeolite physically scatters ultraviolet light, absorbing free radicals generated during use due to thermo-oxidative effects and slowing down the aging process. When the zirconium oxide content is insufficient, enough complementary trapping sites cannot be formed, resulting in a slight decrease in chain reaction blocking efficiency. When the zirconium oxide content is high, the ultraviolet-enhancing shielding ability of magnesium oxide is weakened, leading to a decline in long-term UV aging resistance.
[0021] As a further technical solution, the outer sheath also includes the following components in parts by weight: 2-4 parts plasticizer, 20-30 parts flame retardant, and 1-1.5 parts lubricant.
[0022] As a further technical solution, the antioxidant includes antioxidant 1010 or antioxidant 1076.
[0023] As a further technical solution, the ultraviolet absorber includes ultraviolet absorber UV-531 or ultraviolet absorber UV-327.
[0024] As a further technical solution, the plasticizer includes naphthenic oil or paraffin oil.
[0025] In the outer sheath of the present invention, the plasticizer may be one or more of the conventional plasticizers in the art, such as one or more of naphthenic oil, paraffin oil, and white oil. Preferably, the plasticizer includes naphthenic oil or paraffin oil.
[0026] As a further technical solution, the flame retardant includes magnesium hydroxide and aluminum hydroxide.
[0027] As a further technical solution, the lubricant includes stearic acid or zinc stearate.
[0028] In the outer sheath of the present invention, the lubricant can be one or more of the conventional lubricants in the art, such as stearic acid, zinc stearate, calcium stearate, and polyethylene wax. Preferably, the lubricant includes one of stearic acid and zinc stearate.
[0029] As a further technical solution, fireproof sealant is provided in the gaps between the cable cores and the gaps between the cable cores and the inner lining layer.
[0030] This invention also proposes a method for preparing an aging-resistant aluminum alloy cable, comprising the following steps: An insulation layer is provided outside the aluminum alloy conductor to obtain a cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core to obtain a cable semi-finished product. The components of the outer sheath are mixed evenly and extruded around the cable semi-finished product to obtain the aging-resistant aluminum alloy cable.
[0031] The working principle and beneficial effects of this invention are as follows: In this invention, the addition of zeolite-loaded metal oxides to the outer sheath of aluminum alloy cables can improve the long-term aging resistance of the outer sheath and reduce the amount of small-molecule antioxidants and ultraviolet absorbers required. The metal oxides (zirconia and / or magnesium oxide) present in the zeolite can capture free radicals generated by material degradation during the thermo-oxidative aging process, block the free radical chain reaction, and improve the material's resistance to thermo-oxidative aging. Furthermore, zirconia and / or magnesium oxide can effectively shield ultraviolet radiation, reducing the direct damage of ultraviolet light to the polyethylene molecular chains. The porous structure of zeolite can physically scatter ultraviolet light, further reducing the damage of ultraviolet energy to the matrix. Compared to small-molecule antioxidants, zirconium oxide and / or magnesium oxide are anchored on zeolite, preventing migration, volatilization, or precipitation, thus ensuring long-term stable performance. Zeolite can also adsorb and fix small-molecule antioxidants and UV absorbers in the outer sheath through physical and chemical adsorption, further preventing their migration and precipitation to the material surface under high temperature and UV conditions. This avoids the significant reduction in aging resistance caused by migration of small-molecule antioxidants and UV absorbers during long-term use. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] In the following examples and comparative examples, polyethylene: model LL 8446.21; maleic anhydride-grafted linear low-density polyethylene: model NE062E; 4A zeolite: average particle size of 2μm; clinoptilolite: average particle size of 3μm.
[0034] Example 1 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 90 parts polyethylene, 3 parts maleic anhydride-grafted linear low-density polyethylene, 0.1 parts antioxidant 1010, 0.2 parts ultraviolet absorber UV-327, 3 parts 4A zeolite-supported zirconium oxide, 2 parts naphthenic oil, 10 parts magnesium hydroxide, 10 parts aluminum hydroxide, and 1 part stearic acid. The preparation method of 4A zeolite-supported zirconia includes the following steps: 4A zeolite was added to a 1.0 mol / L HNO3 solution and mixed at 200 rpm for 4.5 h (the mass-to-volume ratio of 4A zeolite to HNO3 solution was 30 g: 90 mL). After centrifugation at 2500 rpm for 6 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 200 rpm for 4.5 h (the mass-to-volume ratio of 4A zeolite to ammonium nitrate solution was 30 g: 90 mL). After centrifugation at 2500 rpm for 6 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated 4A zeolite. Water was added to zirconium nitrate to obtain a 0.05 mol / L zirconium nitrate solution. Pretreated 4A zeolite was added to zirconium nitrate solution (the mass-volume ratio of pretreated 4A zeolite to zirconium nitrate solution was 30 g: 90 mL), the pH was adjusted to 7 with 2.0 mol / L ammonia water, and the solution was soaked at 250 rpm for 6.5 h, dried at 60 °C for 12 h, ground at 600 rpm for 5 min, and finally calcined at 400 °C for 5 h under nitrogen atmosphere to obtain 4A zeolite supported zirconium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0035] Example 2 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 95 parts polyethylene, 4.5 parts maleic anhydride-grafted linear low-density polyethylene, 0.15 parts antioxidant 1010, 0.25 parts ultraviolet absorber UV-531, 4 parts 4A zeolite-supported zirconium oxide, 3 parts naphthenic oil, 12 parts magnesium hydroxide, 13 parts aluminum hydroxide, and 1.3 parts zinc stearate; The preparation method of 4A zeolite-supported zirconia includes the following steps: 4A zeolite was added to a 1.0 mol / L HNO3 solution and mixed at 250 rpm for 4 h (the mass-to-volume ratio of 4A zeolite to HNO3 solution was 30 g: 95 mL). After centrifugation at 3000 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 250 rpm for 4 h (the mass-to-volume ratio of 4A zeolite to ammonium nitrate solution was 30 g: 95 mL). After centrifugation at 3000 rpm for 5 min and washing three times with ultrapure water, it was dried at 110 °C for 6 h to obtain pretreated 4A zeolite. Water was added to zirconium nitrate to obtain a 0.08 mol / L zirconium nitrate solution. Pretreated 4A zeolite was added to zirconium nitrate solution (the mass-volume ratio of pretreated 4A zeolite to zirconium nitrate solution was 30 g: 95 mL), the pH was adjusted to 7 with 2.0 mol / L ammonia water, and the solution was soaked at 250 rpm for 6 h, dried at 70 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under nitrogen atmosphere to obtain 4A zeolite supported zirconium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0036] Example 3 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts 4A zeolite-supported zirconium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. The preparation method of 4A zeolite-supported zirconia includes the following steps: 4A zeolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of 4A zeolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of 4A zeolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated 4A zeolite. Water was added to zirconium nitrate to obtain a 0.1 mol / L zirconium nitrate solution. Pretreated 4A zeolite was added to zirconium nitrate solution (the mass-volume ratio of pretreated 4A zeolite to zirconium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia water, and the solution was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under nitrogen atmosphere to obtain 4A zeolite supported zirconium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0037] Example 4 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts clinoptilolite-supported zirconium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. A method for preparing clinoptilolite-supported zirconia includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Water was added to zirconium nitrate to obtain a 0.1 mol / L zirconium nitrate solution. Pretreated clinoptilolite was added to a zirconium nitrate solution (the mass-to-volume ratio of pretreated clinoptilolite to zirconium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia, and the mixture was impregnated at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under a nitrogen atmosphere to obtain clinoptilolite-supported zirconium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0038] Example 5 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts clinoptilolite-supported magnesium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. A method for preparing clinoptilolite-supported magnesium oxide includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Water was added to magnesium nitrate to obtain a 0.1 mol / L magnesium nitrate solution. Pretreated clinoptilolite was added to magnesium nitrate solution (the mass-volume ratio of pretreated clinoptilolite to magnesium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia water, and the mixture was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under a nitrogen atmosphere to obtain clinoptilolite-supported magnesium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0039] Example 6 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 1 part clinoptilolite-supported zirconium oxide, 4 parts clinoptilolite-supported magnesium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. A method for preparing clinoptilolite-supported zirconia includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Water was added to zirconium nitrate to obtain a 0.1 mol / L zirconium nitrate solution. Pretreated clinoptilolite was added to zirconium nitrate solution (the mass-volume ratio of pretreated clinoptilolite to zirconium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia water, and the mixture was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under nitrogen atmosphere to obtain clinoptilolite-supported zirconium oxide. A method for preparing clinoptilolite-supported magnesium oxide includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Water was added to magnesium nitrate to obtain a 0.1 mol / L magnesium nitrate solution. Pretreated clinoptilolite was added to magnesium nitrate solution (the mass-volume ratio of pretreated clinoptilolite to magnesium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia water, and the mixture was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under a nitrogen atmosphere to obtain clinoptilolite-supported magnesium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0040] Example 7 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts clinoptilolite-supported zirconium oxide and magnesium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. A method for preparing clinoptilolite-supported zirconium oxide and magnesium oxide includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min, and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min, and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Adding zirconium nitrate and magnesium nitrate to water (the molar ratio of magnesium nitrate to zirconium nitrate is 4:1) yields a 0.1 mol / L metal salt solution. Pretreated clinoptilolite was added to a metal salt solution (the mass-volume ratio of pretreated clinoptilolite to metal salt solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia, and the solution was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under a nitrogen atmosphere to obtain clinoptilolite-supported zirconium oxide and magnesium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0041] Example 8 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts clinoptilolite-supported zirconium oxide and magnesium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. A method for preparing clinoptilolite-supported zirconium oxide and magnesium oxide includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min, and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min, and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Adding zirconium nitrate and magnesium nitrate to water (the molar ratio of magnesium nitrate to zirconium nitrate is 3:1) yields a 0.1 mol / L metal salt solution. Pretreated clinoptilolite was added to a metal salt solution (the mass-volume ratio of pretreated clinoptilolite to metal salt solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia, and the solution was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under a nitrogen atmosphere to obtain clinoptilolite-supported zirconium oxide and magnesium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0042] Example 9 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts clinoptilolite-supported zirconium oxide and magnesium oxide, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. A method for preparing clinoptilolite-supported zirconium oxide and magnesium oxide includes the following steps: Clinoptilolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min, and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of clinoptilolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min, and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated clinoptilolite. Adding zirconium nitrate and magnesium nitrate to water (the molar ratio of magnesium nitrate to zirconium nitrate is 2:1) yields a 0.1 mol / L metal salt solution. Pretreated clinoptilolite was added to a metal salt solution (the mass-volume ratio of pretreated clinoptilolite to metal salt solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia, and the solution was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under a nitrogen atmosphere to obtain clinoptilolite-supported zirconium oxide and magnesium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0043] Comparative Example 1 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.2 parts antioxidant 1076, 0.3 parts ultraviolet absorber UV-531, 5 parts 4A zeolite, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. The preparation method of 4A zeolite-supported zirconia includes the following steps: 4A zeolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of 4A zeolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of 4A zeolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated 4A zeolite. Water was added to zirconium nitrate to obtain a 0.1 mol / L zirconium nitrate solution. Pretreated 4A zeolite was added to zirconium nitrate solution (the mass-volume ratio of pretreated 4A zeolite to zirconium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia water, and the solution was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under nitrogen atmosphere to obtain 4A zeolite supported zirconium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0044] Comparative Example 2 An aging-resistant aluminum alloy cable comprises, from the inside out, a cable core, an inner lining layer, a fire-resistant layer, and an outer sheath; the cable core comprises, from the inside out, an aluminum alloy conductor and an insulation layer. The outer sheath comprises the following components in parts by weight: 100 parts polyethylene, 6 parts maleic anhydride-grafted linear low-density polyethylene, 0.4 parts antioxidant 1076, 0.6 parts ultraviolet absorber UV-531, 4 parts paraffin oil, 15 parts magnesium hydroxide, 15 parts aluminum hydroxide, and 1.5 parts zinc stearate. The preparation method of 4A zeolite-supported zirconia includes the following steps: 4A zeolite was added to a 1.0 mol / L HNO3 solution and mixed at 300 rpm for 3.5 h (the mass-to-volume ratio of 4A zeolite to HNO3 solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was mixed with a 1 mol / L ammonium nitrate solution at 300 rpm for 3.5 h (the mass-to-volume ratio of 4A zeolite to ammonium nitrate solution was 30 g: 100 mL). After centrifugation at 3500 rpm for 5 min and washing three times with ultrapure water, it was dried at 100 °C for 7 h to obtain pretreated 4A zeolite. Water was added to zirconium nitrate to obtain a 0.1 mol / L zirconium nitrate solution. Pretreated 4A zeolite was added to zirconium nitrate solution (the mass-volume ratio of pretreated 4A zeolite to zirconium nitrate solution was 30 g: 100 mL), the pH was adjusted to 8 with 2.0 mol / L ammonia water, and the solution was soaked at 250 rpm for 6.5 h, dried at 80 °C for 10 h, ground at 600 rpm for 5 min, and finally calcined at 450 °C for 4 h under nitrogen atmosphere to obtain 4A zeolite supported zirconium oxide. A method for preparing an aging-resistant aluminum alloy cable includes the following steps: An insulation layer is set outside the aluminum alloy conductor to obtain the cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the cable core. Fireproof putty is applied to the gaps between the cable cores and the gaps between the cable core and the inner lining layer to obtain a semi-finished cable. The components of the outer sheath are mixed evenly and extruded onto the outside of the cable semi-finished product to obtain an aging-resistant aluminum alloy cable.
[0045] Experimental Example 1 The outer sheath of the aging-resistant aluminum alloy cables prepared in Examples 1-3 and Comparative Examples 1-2 was tested for tensile strength according to the method specified in GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The dumbbell-shaped type 1A specimen was selected as the specimen. The thermal aging test was conducted according to the method in GB / T 2951.12-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables - Part 12: General Test Methods - Thermal Aging Test Method", and the tensile strength test after aging was conducted according to the above method. The aging resistance test method was the air oven aging method, with a temperature of 100℃ and a time of 168h and 336h. The tensile strength test after aging was conducted according to the method specified in GB / T 16422.3-2022 "Laboratory Light Source Exposure Test Methods for Plastics - Part 3: Fluorescent Ultraviolet Lamps". The lamp type was UVA-340 (Type 1A), cycle number was 1, and the cycles were 28 and 42. The test results are shown in Table 1. Wherein, the change rate of tensile strength = (tensile strength after aging treatment - tensile strength before aging) / tensile strength before aging × 100%; Table 1. Test results of the outer sheath performance of the aging-resistant aluminum alloy cables prepared in Examples 1-3 and Comparative Examples 1-2
[0046] Comparing Examples 1-3 and Comparative Examples 1-2, the difference in the decrease in tensile strength of the outer sheath of the aging-resistant aluminum alloy cables prepared in Examples 1-3 and Comparative Examples 1-2 after 168 hours of heat aging treatment or 28 cycles of ultraviolet aging treatment was not significant. However, after 336 hours of hot air treatment or 42 cycles of ultraviolet aging treatment, the decrease in tensile strength of the outer sheath of the aging-resistant aluminum alloy cables prepared in Comparative Examples 1-2 was significantly higher than that in Examples 1-3. This indicates that the addition of zeolite-loaded metal oxides can improve the long-term aging resistance of the outer sheath of aluminum alloy cables, thereby improving the long-term aging resistance characteristics of aluminum alloy cables.
[0047] Experimental Example 2 The outer sheath of the aging-resistant aluminum alloy cables prepared in Examples 3 to 9 was tested for tensile strength according to the method specified in GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The dumbbell-shaped type 1A specimen was selected as the specimen. The thermal aging test was conducted according to the method in GB / T 2951.12-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables - Part 12: General Test Methods - Thermal Aging Test Method", and the tensile strength test after aging was conducted according to the above method. The aging resistance test method was the air oven aging method, with a temperature of 100℃ and a time of 336h. The tensile strength test after aging was conducted according to the method specified in GB / T 16422.3-2022 "Laboratory Light Source Exposure Test Methods for Plastics - Part 3: Fluorescent Ultraviolet Lamps". The lamp type was UVA-340 (Type 1A), cycle number was 1, and the cycle was 42 times. The test results are shown in Table 2. Wherein, the change rate of tensile strength = (tensile strength after aging treatment - tensile strength before aging) / tensile strength before aging × 100%; Table 2. Test results of the outer sheath performance of the aging-resistant aluminum alloy cables prepared in Examples 3-9
[0048] 1. Compared with Examples 4 to 9, the outer sheath of the aging-resistant aluminum alloy cable prepared in Example 7 showed a lower decrease in tensile strength after 42 cycles of hot air treatment or ultraviolet aging treatment for 336 hours. This indicates that the zeolite-loaded metal oxide is clinoptilolite-loaded zirconium oxide and magnesium oxide, which can further improve the long-term aging resistance of the outer sheath of the aluminum alloy cable, thereby further improving the long-term aging resistance characteristics of the aluminum alloy cable.
[0049] 2. Compared with Examples 7 to 9, the outer sheath of the aging-resistant aluminum alloy cable prepared in Example 8 showed a lower decrease in tensile strength after 42 cycles of hot air treatment or ultraviolet aging treatment for 336 hours. This indicates that when the molar ratio of magnesium salt to zirconium salt is 3:1, the effect of improving the long-term aging resistance of the outer sheath of the aluminum alloy cable is optimal.
[0050] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An aging-resistant aluminum alloy cable, characterized in that, From the inside out, it includes the cable core, inner lining layer, fire-resistant layer, and outer sheath; The cable core consists of an aluminum alloy conductor and an insulation layer from the inside out; The outer sheath comprises the following components in parts by weight: 90-100 parts polyethylene, 3-6 parts maleic anhydride-grafted linear low-density polyethylene, 0.1-0.2 parts antioxidant, 0.2-0.3 parts ultraviolet absorber, and 3-5 parts zeolite-supported metal oxide. The raw materials for the zeolite-supported metal oxide include metal salts and zeolite; the metal salts include magnesium salts and / or zirconium salts.
2. The aging-resistant aluminum alloy cable according to claim 1, characterized in that, The method for preparing the zeolite-supported metal oxide includes the following steps: S1. Add zeolite to an acidic solution and mix once, centrifuge and wash once, then mix with ammonium nitrate solution a second time, centrifuge a second time, wash and dry to obtain pretreated zeolite; add water to metal salt to obtain metal salt solution; S2. Add the pretreated zeolite to the metal salt solution, adjust the pH to 7-8, impregnate, dry, grind, and calcine to obtain the zeolite-loaded metal oxide.
3. The aging-resistant aluminum alloy cable according to claim 2, characterized in that, The zeolite includes 4A zeolite or clinoptilolite; The mass-to-volume ratio of the zeolite to the acidic solution is 30g:90~100mL; The mass-to-volume ratio of the zeolite to the ammonium nitrate solution is 30g:90~100mL; The concentration of the metal salt solution is 0.05~0.1 mol / L.
4. The aging-resistant aluminum alloy cable according to claim 2, characterized in that, The mass-to-volume ratio of the pretreated zeolite to the metal salt solution is 30g:90~100mL; The soaking time is 5.5~6.5 hours; The calcination temperature is 400~450℃, the time is 4~5h, and the atmosphere is nitrogen.
5. The aging-resistant aluminum alloy cable according to claim 1, characterized in that, When the metal salt includes magnesium salt and zirconium salt, the molar ratio of magnesium salt to zirconium salt is 2~4:
1.
6. The aging-resistant aluminum alloy cable according to claim 1, characterized in that, The outer sheath also includes the following components in parts by weight: 2-4 parts plasticizer, 20-30 parts flame retardant, and 1-1.5 parts lubricant.
7. The aging-resistant aluminum alloy cable according to claim 1, characterized in that, The antioxidant includes antioxidant 1010 or antioxidant 1076; The ultraviolet absorber includes ultraviolet absorber UV-531 or ultraviolet absorber UV-327.
8. The aging-resistant aluminum alloy cable according to claim 6, characterized in that, The plasticizer includes naphthenic oil or paraffin oil.
9. The aging-resistant aluminum alloy cable according to claim 6, characterized in that, The flame retardant includes magnesium hydroxide and aluminum hydroxide; The lubricant includes stearic acid or zinc stearate.
10. A method for preparing an aging-resistant aluminum alloy cable, used to prepare the aging-resistant aluminum alloy cable according to any one of claims 1 to 9, characterized in that, Includes the following steps: An insulation layer is provided outside the aluminum alloy conductor to obtain a cable core. An inner lining layer and a fire-resistant layer are sequentially wrapped around the outside of the cable core to obtain a cable semi-finished product. The components of the outer sheath are mixed evenly and extruded around the cable semi-finished product to obtain the aging-resistant aluminum alloy cable.